Potrzebuję na Teraz :)
1. Oblicz
a) (2x-1)+(3x-2)-(4x-6)=
b) 3(a+b)-4(a-b)-5(2a-4b)=
c) 5a-2(3a-7)-3(a-3)-2a=​



Odpowiedź :

Odpowiedź:

a) (2x-1)+(3x-2)-(4x-6)=2x-1+3x-2-4x+6 =1x+3

b) 3(a+b)-4(a-b)-5(2a-4b) = 3 x a + 3 x b - 4 x a - 4 x b - 5 x 2a - 5 x 4b =3a +3b -4a +4b -10a +20b = -11a + 27b

c) 5a-2(3a-7)-3(a-3)-2a = 5a - 2 x 3a - 2 x -7 - 3 x a - 3 x -3 -2= 5a - 6a + 14 - 3a + 9 -2a = -6a + 23

MertB

Cześć!

Szczegółowe wyjaśnienie:

a)

[tex](2x - 1) + (3x - 2) - (4x - 6) = \\ 2x - 1 + 3x - 2 - 4x + 6 \\ x - 1 - 2 + 6 = \\ x + 3[/tex]

b)

[tex]3(a + b) - 4(a - b) - 5(2a - 4b) = \\ 3a + 3b - 4a + 4b - 10a + 20b \\ - 11a + 3b + 4b + 20b = \\ - 11a + 27b[/tex]

c)

[tex]5a - 2(3a - 7) - 3(a - 3) - 2a \\ 5a - 6a + 14 - 3a + 9 - 2a = \\ - 6a + 14 + 9 = \\ - 6a + 23[/tex]